DETERMINISME TEKNOLOGI KOMUNIKASI DAN GLOBALISASI MEDIA TERHADAP SENI BUDAYA INDONESIA (Widyadari : Jurnal Pendidikan, 2021)
The Determinism of Communication Technology and Media Globalization Towards Arts and Indonesian Cuture. This stud focues on the effect of the exposure of media communications technology and the globalization of the art and cuture in Indonesia. Determination of communications tekhology or the exposure of communication tekhology present in the midst of society and influence the wordview and human hebavior in everyday life. Commonication technology and media are a dumvire that connot besprated, bot present complementary. The increasingly rapid devoloment of media and its advancement are along whit the development of Communication technology. The exposure of media and technology affects art and cuture as well as the behavior of people or the Indonesian. Qualitative deskretive analysis is the method of assisment used to uncover the facts, phenomena, variables and circumsyances that occurred while running the research and presenting it as what it is. The variables in thid study are technology media globalization,and Indonesian art and culture of technology and media globalization exposure to the art and culture of Indonesia.